Oral solid self-nanoemulsifying drug delivery systems of candesartan citexetil: formulation, characterization and in vitro drug release studies - Halah Hussein Ali; Ahmed Abbas Hussein (SpringerOpen, 2017)
Abstract Candesartan cilexetil is an ester prodrug antagonist to angiotensin II receptor type 1 (AT1) used in management of many cardiovascular diseases. The absolute bioavailability of candesartan cilexetil is about (14-40%). Therefore, the paper aim was to prepare and evaluate solid self-nanoemulsifying drug delivery systems for candesartan cilexetil in order to improve its solubility, dissolution and stability. Solubility study was run in different vehicles to select the best excipients for dissolving candesartan cilexetil. Pseudo-ternary phase diagrams were constructed at 1:1, 2:1, 3:1 and 4:1 ratios and four formulations were prepared using various concentrations of cinnamon oil, tween 80 with poloxamer 407 mixture and transcutol HP as oil, surfactant mixture and co-surfactant, respectively. After this step about (0.2 milliliter) of each formulation was adsorbed on to two different adsorbent mixtures set which were: avicel 101 with aerosil 200 and avicel 101 with dibasic calcium phosphate anhydrous resulted in eight solid nanoformulations. All prepared formulations were evaluated for particle size distribution, polydispersity index, zeta potential, scanning probe microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray powder diffractometry and in vitro drug dissolution. It was found that release rate and extent for all prepared formulations were significantly higher (p < 0.05) than marketed tablet as well as plain drug powder. It could be concluded from the study that self-nanoemulsifying drug delivery system is a promising approach to improve solubility, wettability, dissolution and stability of candesartan cilexetil.